2018
DOI: 10.1021/acs.molpharmaceut.7b00728
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Human Peptide/Histidine Transporter 1 in Stably Transfected MDCK Cells

Abstract: The proton-coupled oligopeptide transporter PHT1 (SLC15A4), which facilitates cross-membrane transport of histidine and small peptides from inside the endosomes or lysosomes to cytosol, plays an important role in intracellular peptides homeostasis and innate immune responses. However, it remains a challenge to elucidate functional properties of the PHT1 transporter because of its subcellular localization. The purpose of this study was to resort hPHT1 protein from the subcellular to outer cell membrane of MDCK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…SLC15A4, another POT family member, is also localized in endosomes and lysosomes, and has similar transport properties with SLC15A3 9 , 10 . Several studies have reported that SLC15A4 is closely associated with inflammatory diseases such as diabetes, systemic lupus erythematosus and inflammatory bowel disease 11 14 .…”
Section: Introductionmentioning
confidence: 99%
“…SLC15A4, another POT family member, is also localized in endosomes and lysosomes, and has similar transport properties with SLC15A3 9 , 10 . Several studies have reported that SLC15A4 is closely associated with inflammatory diseases such as diabetes, systemic lupus erythematosus and inflammatory bowel disease 11 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A non-volatile SDS solution (0.1%) has been applied in previous studies for the preparation of cell extracts. [23][24][25] In our preliminary experiments, the applicability of SDS as the presence of halogen, but the exact mechanism was not clear.…”
Section: Discussionmentioning
confidence: 82%
“…However, to decrease volatilization at room temperature, lysing of cells with organic solvents and further scraping of cells from plates are usually conducted on ice, a procedure that is elaborate and time‐consuming. A non‐volatile SDS solution (0.1%) has been applied in previous studies for the preparation of cell extracts 23–25 . In our preliminary experiments, the applicability of SDS (0.025%, 0.05% and 0.1%), sodium acetate (0.2 M) solution and methanol (100%) to lyse cells was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…β-Ala-Lys-AMCA uptake peaked at pH 6.5, which was consistent with previous studies that the maximal uptake of Gly-Sar was observed at pH 6.5 in PC-3 cells, MDCK cells, and LLC-PK1 cells transfected with PepT2 from different species. 2,18,19 Our transport-kinetics assay showed that the transport of β-Ala-Lys-AMCA in BMECs fit into Michaelis−Menten type kinetics and had a K m of 82 ± 18 μM and a V max of 124 ± 11 pmol/min per milligram of protein, which are similar to previously reported values in mouse splenic macrophages (K m = 75.5 μM and V max = 25.4 pmol/min per milligram of protein). 20 These low K m and V max values suggest that the transport of β-Ala-Lys-AMCA in BMECs is mainly mediated by PepT2, which is a highaffinity and low-capacity transporter.…”
Section: ■ Discussionmentioning
confidence: 99%